TRANSFORMATION OF THE WASTE MANAGEMENT SYSTEM IN UKRAINE ON THE BASIS OF CIRCULAR ECONOMY - Lutsiv, Nataliia; Kapral , Andriy (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
Strategic priorities of the transformation of the municipal waste management system in Ukraine in the context of European integration on the basis of a circular economy are presented in the paper. Based on a comparative analysis, methodological discrepancies between national recycling indicators and the European recycling rate indicator were identified, which complicates objective monitoring of reforms. The need to implement the waste hierarchy of Directive 2008/98/EC and economic instruments (EPR, DRS, PAYT) in combination with the transition to regional clustering is substantiated. The generalization of international technical assistance practices (U-LEAD, GIZ, USAID, Sida) confirms the key role of intermunicipal cooperation in the development of infrastructure and the integration of demolition waste into green recovery processes.